Ansiedade da puérpera e amamentação no período pós-parto: revisão integrativa - Anjos, Adriane Machado dos (Universidade do Vale do Rio dos Sinos, 2021)
The postpartum period is the ideal time to create a bond between the binomial and also to stimulate and start the breastfeeding process. The cycle of changes and uncertainties generates different feelings in women, including anxiety. To analyze the scientific production over the anxiety of those who have recently given birth or those who are breastfeeding on the postpartum period. It is about a review of literature. The research took place between September and October of 2021, with the deta base BDenf – BIREME (Base de Dados de Enfermagem, via BVS), Literatura Latino- Americana e do Caribe em Ciências da Saúde (LILACS, via BVS), e Índice Cumulativo de Literatura de Enfermagem e Saúde Aliada (CINAHL).The research resulted in 52 articles, which 11 attended to this study. It was divided in two sub-categories: the nursing team in the postpartum period, which highlighted the importance of professionals promoting support and breastfeeding protection, as well as, the need of a bigger and singular human interaction to reduce anxiety and increase self confidence to the binomial and the view breastfeeding in thepostpartum of those who have recentlygiven birth, it brought the anxiety related to ambiguous feelings in the postpartum, the absence od protagonism in the breastfeeding, the need for support of the team that takes care, benefits of the partner in the process. The mother's anxiety can negatively influence breastfeeding. The presence of nursing in the postpartum period is of fundamental importance to guarantee the role of women. The postpartum women's speech brings the appearance of insecurity and anxiety due to the need to be able to contribute with their experiences. The need for training of the teams that provide care to the binomial becomes relevant, ensuring the role of the mother in the process of establishing breastfeeding
Keywords: Aleitamento materno; Enfermagem; Ansiedade; Período pós-parto; Breastfeeding; Nursing; Anxiety; Postpartum period